Youth transitions in young mothers: a study on the importance of the care network in the Municipality of Avellaneda (Praxis Educativa, 2022)
The present work deals with the youth transitions of young mothers, mediated by a state device such as municipal kindergartens, which open possibilities for them in terms of trajectory. The results of a study carried out through interviews with directors of municipal gardens and young mothers who attend them are presented, through a qualitative methodology that combined virtual and face-to-face interviews. The information collected was processed considering the most important variables of the survey. From its analysis, the main results are presented. The article also reviews the current situation of the initial level, showing the inequality in access to this level by the most vulnerable sectors, describes the network of kindergartens in Avellaneda and presents a theoretical framework for the analysis of the interviews. mentioned. Finally, it offers final comments to continue the theoretical discussions.
Keywords: YOUTH; TRANSITIONS; EDUCATION; GENDER; SYSTEMS OF CARE